Albumin-bilirubin score for predicting the in-hospital mortality of acute upper gastrointestinal bleeding in liver cirrhosis: A retrospective study - Zou, Deli; Qi, Xingshun; Zhu, Cuihong; Ning, Zheng; Hou, Feifei; Zhao, Jiancheng; Peng, Ying; Li, Jing; Deng, Han; Guo, Xiaozhong (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: The albumin-bilirubin (ALBI) score is a new model for assessing the severity of liver dysfunction. In the present study, we aimed to retrospectively compare the performance of ALBI with Child-Pugh and the model for end-stage liver disease (MELD) scores for predicting the in-hospital mortality of acute gastrointestinal bleeding (AUGIB) in liver cirrhosis. Materials and Methods: All cirrhotic patients with AUGIB were eligible, provided they had the data needed to determine the ALBI score. Areas under the receiving-operator characteristics curve (AUC) are reported. Results: Overall, 631 patients were included. In all the included patients, the AUC of the ALBI, Child-Pugh, and MELD scores were 0.808, 0.785 (p=0.5831), and 0.787 (p=0.7033), respectively. In patients with only hepatitis B virus-related liver cirrhosis, the AUC of the ALBI, Child-Pugh, and MELD scores were 0.865, 0.836 (p=0.6064), and 0.818 (p=0.6399), respectively. In patients with only alcohol-related liver cirrhosis, the AUC of the ALBI, Child-Pugh, and MELD scores were 0.869, 0.860 (p=0.9003), and 0.801 (p=0.5548), respectively. In patients treated with endoscopic therapy for AUGIB, the AUC of the ALBI, Child-Pugh, and MELD scores were 0.873, 0.884 (p=0.7898), and 0.834 (p=0.5531), respectively. Conclusion: The prognostic performance of the ALBI score was comparable with that of the Child-Pugh and MELD scores for predicting the in-hospital mortality of AUGIB in liver cirrhosis.